Changes in lipoprotein subfractions following menopause in the Longitudinal Study of Adult Health (ELSA-Brasil). (December 2019) - Fonseca, Marília I.H.; de Almeida-Pititto, Bianca; Bensenor, Isabela M.; Toth, Peter P.; Jones, Steven R.; Blaha, Michael J.; Lotufo, Paulo A.; Kulkarni, Krishnaji R.; Ferreira, Sandra R.G.; ,
Highlights: There is little evidence on the association between duration of menopause and lipoprotein subfractions. A more deleterious lipid panel was observed in the first two years after menopause. No associations were found between time since menopause and lipoprotein cholesterol subfractions. Menopause is accompanied by higher triglyceride-rich lipoprotein subfractions. Abstract: Introduction: It is unclear how aging and menopause-induced lipid changes contribute to the elevated cardiovascular risk in menopausal women. We examined the association between lipid profiles and menopausal status and duration of menopause in the Longitudinal Study of Adult Health (ELSA-Brasil). Methods: This is a cross-sectional analysis of baseline data from women in the ELSA-Brasil, stratified by duration of menopause into 5 groups: pre-menopause, <2 years, 2–5.9 years, 6–9.9 years and ≥10 years of menopause, excluding menopause <40 years or of non-natural cause; also excluded were women using lipid-lowering drugs or hormone replacement. Comparisons were performed using ANOVA with Bonferroni correction. Associations of menopause categories and time since menopause with lipid variables obtained by vertical auto-profile were tested using multiple linear regression. Results: From 1916 women, postmenopausal groups had unadjusted higher total cholesterol, LDL-c, real LDL-c, IDL-c, VLDL-c, triglycerides, non-HDL-c, VLDL3 -c, triglyceride-rich lipoprotein remnants (TRL-c) and buoyant LDL-c concentrations than pre-menopausal women, with no difference among postmenopausal groups. In multiple linear regression, duration of menopause <2 years was significantly associated with TRL-c [7.21 mg/dL (95% CI 3.59–10.84)] and VLDL3-c [2.43 mg/dL (95%CI 1.02–3.83)]. No associations of menopausal categories with HDL-c or LDL-c subfractions were found, and nor were associations of time since menopause with lipid subfractions. Conclusions: In a large sample of Brazilian women, deterioration of the lipid profile following menopause was confirmed, which could contribute to the increased cardiovascular risk. Our findings suggest a postmenopausal elevation in triglyceride-rich lipoprotein remnants. How lipoprotein subfractions change after the onset of menopause warrants investigation in studies with appropriate designs.